The relationships among attachment style, willingness to express negative emotion, and social anxiety in young adults. - Torrecampo, Ana Patricia
The purpose of the current study was to examine the relationships among attachment style, willingness to express negative emotion, and social anxiety. A survey was done to examine the relationship of these variables. There is a difference on young adults? willingness to express negative emotion at different attachment categories. Social anxiety is not associated with willingness to express negative emotion. There is a difference on the levels of social anxiety at different attachment categories